The Effect of The Predict Observe Explain Strategy on Reducing Misconceptions About Light In Elementary Schools - Kurniasari, Herlin; Nugroho, Ikhlasul Ardi (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to determine the effect of the Predict–Observe–Explain (POE) strategy on reducing misconceptions about light among fifth-grade elementary school students. This study describes empirical evidence of differences in the reduction of misconceptions between classes that received instruction using the POE strategy and classes that received instruction through teacher demonstrations. This study used a quantitative method with a quasi-experimental design, specifically a Nonequivalent Control Group Design, conducted at Demangan State Elementary School in the odd semester of the 2025/2026 academic year. The research subjects consisted of 52 fifth-grade students divided into an experimental class and a control class. Misconception data were collected through a validated two-tier diagnostic test, and the results showed that the validity was in the valid category. The reliability estimate of the misconception instrument was obtained through the Cronbach's Alpha test with a coefficient of 0.832, which is classified as high. Data analysis techniques included prerequisite tests (normality and homogeneity) and difference tests using independent t-tests for misconception reduction. The results showed that the average misconception reduction score in the experimental class increased from 44.35 on the pretest to 70.65 on the posttest, an increase of 26.30, while the control class only increased from 48.73 to 56.38, an increase of 7.65. The hypothesis test results showed a Sig. (2-tailed) value < 0.05 for both variables, so Ha was accepted. Thus, it can be concluded that the POE strategy has a significant effect in reducing students' misconceptions about light.